RNAi and Ino80 complex control rate limiting translocation step that moves rDNA to eroding telomeres. Issue 14 (9th July 2021) - Apte, Manasi S; Masuda, Hirohisa; Wheeler, David Lee; Cooper, Julia Promisel
Abstract: The discovery of HAATI rDNA, a telomerase-negative survival mode in which canonical telomeres are replaced with ribosomal DNA (rDNA) repeats that acquire chromosome end-protection capability, raised crucial questions as to how rDNA tracts 'jump' to eroding chromosome ends. Here, we show that HAATI rDNA formation is initiated and limited by a single translocation that juxtaposes rDNA from Chromosome (Chr) III onto subtelomeric elements (STE) on Chr I or II; this rare reaction requires RNAi and the Ino80 nucleosome remodeling complex (Ino80C), thus defining an unforeseen relationship between these two machineries. The unique STE-rDNA junction created by this initial translocation is efficiently copied to the remaining STE chromosome ends, independently of RNAi or Ino80C. Intriguingly, both RNAi and Ino80C machineries contain a component that plays dual roles in HAATI subtype choice. Dcr1 of the RNAi pathway and Iec1 of Ino80C both promote HAATI rDNA formation as part of their respective canonical machineries, but both also inhibit formation of the exceedingly rare HAATI STE (where STE sequences mobilize throughout the genome and assume chromosome end protection capacity) in non-canonical, pathway-independent manners. This work provides a glimpse into a previously unrecognized crosstalk between RNAi and Ino80C in controlling unusual translocation reactions that establish telomere-free linear chromosome ends.